NILAI PENDIDIKAN KARAKTER PADA ANIMASI “NUSSA” (KAJIAN SEMIOTIK SAUSSURE) - Tita Tita Tita; Syihabuddin Syihabuddin (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2023)
This study aims to find out and describe the value of character education in the film "Nussa" based on the Ministry of Education and Culture. The method used in this study is descriptive by analyzing qualitative data. The results showed that the animated film "Nussa" contains all the values of character education in accordance with the Ministry of Education and Culture, namely the value of religious character education, the value of nationalist character education, the value of independent character education, the value of integrity character education and the value of mutual cooperation character education. All types of data containing character education values are adjusted to semiotic studies, namely signifiers and signified. The film can be used as a very educational spectacle for both children who have entered school age or who have not entered school age.